The Role of Endophyte Bacteria in The Growth and Yield of Various Rice Varieties in Rainfed Rice Lands - Wiyono , Wiyono; Ambawati, Galih Saras; Priyadi, Sapto; Daryanti , Daryanti; Aziez, Achmad Fatchul; Ali, Mazhar (Biosaintifika: Journal of Biology & Biology Education, 2024)
Rainfed land typically lacks essential nutrients, including nitrogen. An endophytic bacterial consortium can fix nitrogen from the air, potentially enhancing the growth and yield of lowland rice varieties. The aim of this research was to assess the growth and yield of various lowland rice varieties when treated with a consortium of diazotrophic endophytic bacteria in rainfed land. This study was conducted in rainfed rice fields in Demangan, Sambi, Boyolali, Central Java, Indonesia, to evaluate the growth of rice varieties at different doses of the endophytic bacterial consortium. A completely randomized block design was employed, featuring two factors and three replications. The first factor was the endophytic bacterial consortium, applied at doses of 0, 20, 30, and 40 L/ha/application. The second factor consisted of three rice varieties: Situbagendit, Ciherang, and Mekongga. The results indicated that (1) the dose of endophytic bacteria had a very significant effect on dry shoot weight, dry plant weight, 1,000 grain weight, and panicle length; (2) rice varieties had a significant effect only on fresh shoot weight; and (3) the interaction between the dose of endophytic bacteria and rice varieties did not significantly affect any of the observed parameters. This research suggests that to enhance rice growth and yield in rainfed rice fields, a dose of 40 L/ha/application of the diazotrophic endophytic bacterial consortium is recommended, along with the use of the Situbagendit, Ciherang, or Mekongga varieties.